Pengembangan Media GARDA Untuk Pengenalan Lambang Garuda Pancasila Pada Anak Usia 5-6 Tahun - Rizqi Rahmawati; Ervin Nurul Affrida (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study addresses the limited ability of children aged 5–6 years to recognize the Garuda Pancasila emblem and understand the principles of Pancasila due to predominantly verbal instruction and the lack of concrete learning media. The study aimed to develop and evaluate the feasibility and effectiveness of the GARDA (Garuda Pancasila) learning media for early childhood education. This research employed a Research and Development (R&D) approach using the Borg and Gall model adapted into eight development stages, involving 13 children from Group B1 at Sulthon Aulia Kindergarten. Data were collected through expert validation questionnaires, observations, and pre-test and post-test assessments. The findings indicate that GARDA achieved high feasibility, obtaining 78% from media experts and 94% from material experts. Statistical analysis revealed a significant improvement in children's recognition of the Garuda Pancasila emblem, with a mean gain (Md) of 5 and a t-value of 15.15, exceeding the critical value at the 5% significance level. These findings demonstrate that GARDA not only improves children's cognitive achievement in recognizing national symbols but also provides meaningful, concrete, and interactive learning experiences consistent with the cognitive characteristics of early childhood. The novelty of this study lies in the development of an acrylic magnetic learning medium integrating visual-symbolic activities with Pancasila character education. The study contributes to strengthening the body of knowledge on concrete learning media for civic education in early childhood and offers practical guidance for teachers in implementing engaging, child-centered learning to foster national identity from an early age